Experimental study of vortex-induced vibration of a twin-tube submerged floating tunnel segment model. (April 2020) - Deng, Shi; Ren, Haojie; Xu, Yuwang; Fu, Shixiao; Moan, Torgeir; Gao, Zhen
Abstract: The cross-flow vortex-induced vibration features of a submerged floating tunnel element, which is composed of two rigidly connected cylinders in a tandem configuration, were investigated via a self-oscillation model test in a steady flow. The Reynolds number ranged from 2 × 10 4 to 9 × 10 4, and the ratio of the center-to-center distance between the two cylinders and cylinder diameter varied within a range of 2-4. The vortex induced vibration responses and lift forces on the up- and downstream cylinders were studied under different spacing ratios and compared with those on a single cylinder. The results show that the spacing ratio plays an important role in VIV until the ratio reaches 4. For a small spacing ratio, a significant difference between the lift forces on the up- and downstream cylinders appears and induces a large torsional moment. For the convenience of engineering application, a torsional coefficient was proposed. The maximum torsional coefficient can reach 2.9, 1.2 and 0.98 for spacing ratios of 2, 3 and 4 at the reduced velocity of 5, respectively. Considering the vortex induced vibration responses as well as the torsional moment, a spacing ratio of 3 was recommended for tandem floating tunnel design. Highlights: Self-oscillation test of a twin-tube submerged floating tunnel segment model. Lift forces on stationary and self-oscillation twin-cylinder are compared. A torsional moment is induced due to the difference of lift force on the cylinders. Spacing ratio heavily affects the vortex induced response, lift and torsion.